Bangladeshi medical students intention to use electronic health record system in their medical practice - Sakib, Md Nazmus (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2016)
Electronic Health Record (EHR) is a computerized system that collect, store and display the data of patients. The use of EHR systems is increasing globally and numbers of countries, both developed and developing, have invested in EHR with a hope of developing their health sector. Accordingly, Bangladesh, a developing country, has shown its keen interest on digitization of health sector. However, very limited information is available on medical professionals' perception towards EHR. Therefore, the current study aims to understand the level of behavioural intention towards EHR among medical students of two selected medical colleges in Bangladesh. The study also investigates the predictors of behavioural intention and moderation effects of gender and age on the relationship between the predictors and the behavioural intention of those medical college students towards EHR adoption. The study adapts Unified Theory of Acceptance and Use of Technology (UTAUT) to match the context. Self-administered questionnaire survey method was used to collect among 238 medical students from the two selected medical colleges using convenient sampling. Upon completion of data collection, the data were analysed using SPSS 20. After data screening and data reduction processes, descriptive analysis, correlation analysis, and multiple regression analysis were performed to achieve the research objectives. The findings indicate that the medical college students express a moderate level of EHR acceptance while all the predictors considered in this study, performance expectancy, effort expectancy, and social influence, became prominent predictors. However, gender and age did not moderate any relationship. The findings of this study might help the policy makers in Bangladesh in their strategy formulation, especially in the health sector, in the future.